Nest-leaving in the Starling Sturnus vulgaris: an example of parent-offspring conflict? - Ottosson, Ulf (Ornis Svecica, 1999)
It has been suggested that there will be a conflict not only between parent-offspring but also between siblings, about when to leave the nest. To investigate which part of the family initiates nest-leaving Starling nestboxes, with individually marked nestlings, were observed prior to, during and after nestlings had started to leave the nest. Parents may initiate nest-leaving by decreasing the provisioning rate. It is suggested that the time of fledging is determined by sibling competition and the trade off between the possibility to be fed inside the nestbox or outside.